Strategies to Strengthen Islamic Character through Islamic Education Learning Based on Artificial Intelligence - Rahman, Abdul; Nasution, Baktiar (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
The development of digital technology, especially in the field of artificial intelligence (AI), has created new opportunities to improve the quality of Islamic Religious Education (PAI) learning. One important opportunity in the use of AI for PAI learning is strengthening students’ Islamic character. This study aims to formulate AI-based PAI learning strategies to instill Islamic values such as honesty (ṣidq), faith (īmān), responsibility (amānah), and social attention (khidmah). The method used in this study is qualitative through a literature review approach based on various academic sources that discuss the use of AI in education and the formation of Islamic character. The data were analyzed descriptively to identify the forms, strategies, and implications of AI integration in PAI learning activities. The results of the literature review indicate that AI can support the development of learning media and learning services in PAI, including AI-assisted presentations and visual materials as well as AI-supported learning interactions. The use of AI-based media enables teachers to deliver Islamic moral and spiritual values through presentations, infographics, visual narratives, and reflective videos that are more engaging and easier for students to understand. In addition, AI has the potential to facilitate learning that is more adaptive and can be adjusted to students’ needs and characteristics. In conclusion, integrating AI in PAI learning, particularly to support the development of learning media and adaptive learning experiences, has the potential to strengthen students’ Islamic character. At the same time, implementation still requires adequate infrastructure and stakeholder readiness so that AI functions as a supportive tool and does not replace moral guidance in Islamic education.